Analysis of Calls to Vision Rehabilitation Center during COVID-19 - Abhijeet Beniwal; Suraj Singh Senjam (Delhi Journal of Ophthalmology)
Background: People with disabilities, including blindness, were more likely to be impacted by the COVID-19 pandemic than people without disabilities. The particulars of the callers with visual disabilities, and their reasons could help us to understand their concerns during the COVID-19 emergency lockdown. This paper reported various reasons given by the callers who were visually disabled to the hotline of visual rehabilitation services during the lockdown period. Methodology: A retrospective review of data maintained in the telerehabilitation register for people with visual disabilities of a tertiary eye care center in north India was done from April 19, 2021, to May 27, 2021 (lockdown period). Age, gender, self-reported visual acuity, and diagnosis were extracted from the register. An inductive content analysis assessed the callers’ reasons and presented. Results: A total of 101 callers were noted with males predominant (79.2%), over half of the callers aged between 16 and 25 years. Nearly half of them reported that their visual acuity was <3/60 in both eyes. Retinitis pigmentosa (14.2%), retinal detachment (6.1%), parents of stage 5 retinopathy of prematurity (7.1%), and heredomacular degeneration (5.1%) optic atrophy (4.0%) were common ocular problems as indicated by the callers. The most common reason for calls was issues related to disability certificates (30.7%), followed by calls to avail general eye care (20.9%) and low vision rehabilitation consultation (20.2%). Other reasons for calls were related to admission to vocational training centers (7.8%), schools for the blind (6.2%), and livelihood support during the lockdown (3.1%), respectively. Conclusions: During the emergency COVID-19 lockdown period, a great majority of people with visual disabilities needed services other than eye care. Disability certificate was the most concern among the callers.